A review on the application of natural based plasticizer for polyvinyl chloride / Nik Adriana Rosli - Rosli, Nik Adriana (2022)
Plasticizers are chemical additives added to polymers to obtain desired mechanical properties as well as their processability and ductility. These properties result from the bonding of plasticizer and polymer molecules under plasticization’s theory. The most commonly used plasticizer is phthalate. However, due to its toxicity which often makes people anxious to use it, plasticization is prohibited. Another alternative is to use natural based materials as plasticizer to polyvinyl chloride (PVC). Natural based plasticizers offer the same properties and functions as other plasticizers, but they are naturally plant-derived and have low toxicity. Examples of natural based plasticizers that can be used are epoxidized soybean oil (ESBO), epoxidized linseed oil (ELO), epoxidized castor oil (ECO), epoxidized sunflower oil (ESO) and fatty acid esters. The most commonly used plasticizer for PVC is ESBO as it has good compatibility with PVC as well as its ability in increasing its flexibility.